Quiet Quitting: Sintesis Literatur Sistematis Berbasis Job Demands-Resources Theory dan Agenda Riset Sektor Publik - Rengganis Nurmalasari; Andre Dwijanto Witjaksono; Anang Kistyanto (FEB Universitas Maritim Semarang, 2026)
Quiet quitting has emerged as an important issue in post-pandemic human resource management, reflecting employees' tendency to remain formally employed while limiting their contributions to minimum job requirements. This article aims to synthesize the literature on the relationships among role ambiguity, perceived organizational support, job burnout, and quiet quitting using the Job Demands-Resources Theory. This study employed a Systematic Literature Review guided by PRISMA 2020. Literature searches were conducted from February to May 2026, mainly through Scopus, complemented by other academic databases and snowballing. From 50 identified articles, 17 core articles were analyzed using thematic synthesis, while 8 articles were used as theoretical, methodological, and measurement references. The synthesis shows that quiet quitting is a withdrawal behavior distinct from actual quitting and turnover intention. Role ambiguity can be positioned as a hindrance job demand, while perceived organizational support functions as a job resource whose effectiveness may vary across work contexts. Job burnout appears as a potential psychological mechanism linking job demands, organizational support, and quiet quitting, although empirical evidence on its mediating role remains limited. Among the 17 core articles, only one directly examined public employees. Therefore, this article does not claim generalization to the public sector, but proposes a future research agenda on quiet quitting in public organizations.